Implementasi Penggunaan Platform Scalev dalam Kampanye Digital sebagai Strategi Digital Marketing - Maya Karina; Alshaf Pebrianggara (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the utilization of the Scalev platform as a landing page in digital marketing activities at Human Capital University. A landing page functions as a structured medium for presenting service information while simultaneously encouraging prospective users to take decisive actions, such as completing registration or making purchases. The primary objective of this study is to understand the implementation process of the landing page and to identify challenges encountered during its early adoption phase. A qualitative approach was employed, with data collected through observation and documentation conducted throughout the campaign period. The findings indicate that both visitor volume and transaction rates had not yet reached a stable level, largely attributable to inconsistent content distribution across social media platforms. This instability directly affected the incoming traffic to the landing page and consequently influenced the overall conversion rate. The study further affirms that the effectiveness of a landing page is not solely determined by the visual quality of the page itself, but is also shaped by the consistency of promotional activities, the clarity of the message conveyed, and the precision of audience segmentation. Therefore, the implementation of the Scalev platform should be accompanied by periodic evaluation and continuous strategic adjustment to effectively support the achievement of digital marketing objectives in service-based organizations.